Sistem Tanda Tangan Digital Internal Divisi TI Menggunakan Metode Rapid Application Development (RAD) - Muhamad Alda; Syafhira Ananda Galasca; Nora Asyiqin; Dariana Tanjung (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
At PT Bank Sumut currently, signing is still done manually to ensure that the document is genuine by the relevant official using a wet pen and requires a procedure that is quite long and easily manipulated which can cause the signature to be considered valid and reduce the credibility of the signature. . With the development of technology, moving from signatures that were previously done manually to more modern methods with technology. A digital signature information system encapsulates a series of processes involving the creation, storage and verification of digital signatures. This technology utilizes a special cryptographic algorithm that produces a digital signature that is unique and difficult to forge. In addition, security integration in this information system provides guarantees for the validity of digital documents and the identities of the parties involved. The system development model that will be used is the Rapid Application Development (RAD) method. Where Rapid Application Development (RAD) is a linear sequential software development process model that emphasizes rapid development cycles using a component-based construction approach. The results of this research are that all stages of creating a digital signature system have been completely carried out, namely the stages in the RAD (Rapid Application Development) method. With an implementation concept that focuses on automation with information technology, the involvement of human labor can be reduced so that an effective and efficient work environment will be created. In this development, we are required to follow and adapt to technological developments so that daily activities and work can be carried out more quickly and efficiently.